OPTIMALISASI DIGITAL MARKETING UNTUK AGROWISATA DILI VANILI: MENINGKATKAN POPULARITAS DAN PROMOSI ONLINE - Kusumasari , Fitri; Priambodo, Alvian Rafif; Haq, Jelita Arinal; Agustina, Zalfa Nurrahmah; Achmad, Zainal Abidin (JABN, 2025)
The International Community Service Team from the Universitas Pembangunan Nasional “Veteran” Jawa Timur (UPNVJT), consisting of lecturers from Dili University (Undil), UPNVJT lecturers, and UPNVJT students, carried out community service activities at Dili Vanili Agrotourism, Aileu District, Timor Leste. This team designed a digital empowerment program to increase the capacity of local business actors to utilize social media, especially Instagram, as a means of effective and efficient agrotourism promotion. In this activity, the team provided training on digital marketing strategies, including business account management, branding techniques, and creating attractive and communicative visual content. Participants attended training sessions, content creation practices, and direct assistance in managing social media. The activity results showed an increase in followers and audience engagement on the Dili Vanili Instagram account and the quality and intensity of the uploaded digital promotional content. This activity proves that implementing social media-based digital marketing can expand market reach, improve destination image, and build relationships with consumers more effectively. In addition, this program also shows that cross-institutional collaboration in community service activities can encourage digital transformation in the rural agrotourism sector and strengthen the economic empowerment of local communities through technological mastery.